Sustainability of Masonry and Reinforced Concrete Frame Structures. Case Studies. (2016) - Puskás, Attila; Moga, Ligia
Abstract: Structures of buildings are generally not known as sustainable parts of the buildings, their impact being often neglected, even if important economies could be made in the use of the limited limestone resources and in the negative impact of the large quantity of energy on the environment. When establishing the appropriate structural solution for the given theme the main optimization criteria are the realization cost and the construction time, but also the aesthetics of the structure as well as other architectural impacts might count. The paper aims establishing relationship between the studied structural solutions and their environmental impact: reinforced concrete frame structures with masonry infill walls and load bearing masonry walls with reinforced concrete tie-beams and pillars. The paper presents a comparative study on buildings of three to seven stories, generally used for residential applications. For the same building with variable number of stories two different structural solutions are used, obtaining a total of 8 structures to be designed according to the valid Romanian norms. For the structures the environmental impact is assessed, considering the necessary materials for the realization of the studied structures including internal and external walls. Also cost analyses are performed for the obtained results, in order to obtain the correspondence between the environmental impact and the cost of each solution. Results are emphasizing the environmental impact and cost evolution of buildings with increase of stories for the two structural solutions. It can be followed as the environmental impact varies also with the number of stories. Differences appear in all the main LCA indicators considered in the comparison: energy, solid emissions in air and water, natural resources consumption and waste generation. Comparing the results the more sustainable structural solution with less environmental impact can be concluded.